2019
DOI: 10.1167/19.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Visual-oculomotor interactions facilitate consolidation of perceptual learning

Abstract: Visual skill learning is commonly considered a manifestation of brain plasticity. Following encoding, consolidation of the skill may result in between-session performance gains. A great volume of studies have demonstrated that during the offline consolidation interval, the skill is susceptible to external inputs that modify the preformed representation of the memory, affecting future performance. However, while basic visual perceptual learning is thought to be mediated by sensory brain regions or their higher-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Oculomotor learning is known to benefit from sleep (e.g. Albouy et al., 2006), and it has recently been demonstrated that training and re‐activating an unrelated oculomotor memory can enhance TDT performance (Klorfeld‐Auslender & Censor, 2019). By effectively suppressing oculomotor learning, our protocol may further reduce the number of memory traces that could potentially benefit from sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Oculomotor learning is known to benefit from sleep (e.g. Albouy et al., 2006), and it has recently been demonstrated that training and re‐activating an unrelated oculomotor memory can enhance TDT performance (Klorfeld‐Auslender & Censor, 2019). By effectively suppressing oculomotor learning, our protocol may further reduce the number of memory traces that could potentially benefit from sleep.…”
Section: Discussionmentioning
confidence: 99%
“…This resonates with theories that frame VPL as a change in the readout of visual information by decision-making areas (Dosher & Lu, 2017). A role of motor areas in VPL is further suggested by several behavioral findings, e.g., that motor tasks improve VPL consolidation (Klorfeld-Auslender & Censor, 2019), and, reversely, that VPL can improve oculomotor performance (Szpiro, Spering, & Carrasco, 2014).…”
Section: Introductionmentioning
confidence: 97%